Recommendations for Validation of Automated Viable Cell Counting Methods (Review) - M. A. Vodyakova; N. S. Pokrovsky; E. V. Melnikova; V. A. Merkulov (Разработка и регистрация лекарственных средств, 2023)
Introduction. The quality of viable cell-based products (such as biomedical cell products and advanced therapy medicinal products) must be maintained during the full production cycle to ensure their safety and efficacy for patients. The minimum required number of viable cells is one of the quality control criteria in the final product release specifications. This study looks into the process of validation of automated viable cell counting methods.Text. The study reviewed the latest data on specific validation characteristics for automated cell counters as compared to manual counting methods. We identified the main problems with the validation methods. Based on the review of scientific and regulatory literature, we identified the key validation parameters, methods of their evaluation and measurement, and reporting of results. We described the validation algorithm for an automated cell counter, including such steps as the selection of reference standards, selection of the number of experimental points, experimental design, mathematical evaluation of the obtained results, and determination of the acceptance criteria.Conclusion. Based on the data reviewed, the authors developed recommendations for the validation of automated viable cell counting procedures.